Pemanfaatan Media Presentasi Powerpoint dalam Meningkatkan Minat Belajar Bahasa Inggris Siswa Madrasah Tsanawiyah - Syarif Hidayat; Hesty Widiastuty (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to enhance students' interest in learning English through the utilization of PowerPoint presentations as a teaching medium. The research was conducted at MTs Hidayatul Muhajirin Palangka Raya, involving eighth-grade students. The method employed was a lecture using PowerPoint presentations equipped with audio features. The material taught was